The Influence of Storage of Pawpaw Carica papaya Fruit on the Bioactive Components, Antioxidative Properties and Inhibition of Fe2+-Induced Lipid Peroxidation of Water-Extracts of Pawpaw Seed: Storage Effect on Pawpaw Fruit Properties (Biological Sciences - PJSIR, 2016)
Freshly harvested, matured, newly ripe pawpaw (Carica papaya) fruit (Maradol variety) wasstored at room temperature (27±1 °C) for 7days. The seeds of the freshly harvested and stored pawpawfruit were taken and divided into two groups each; one was dried as dry sample, dry freshly harvestedsample (DFHS) and dry stored sample (DSS) while the other was left as wet sample, wet freshly harvestedsample (WFHS) and wet stored sample (WSS). The bioactive components, antioxidative properties andinhibition of Fe2+ induced lipid peroxidation activity of the water extract of the seed were investigated.Storage of pawpaw fruit caused a significant increase in ascorbic acid and flavonoid content of the pawpawseed in both dry and wet samples but only in dry stored sample significant increase in the phenol contentof the seed was observed. The dried pawpaw seed DFHS and DSS showed stronger inhibition of Fe2+induced lipid peroxidation activities.